A canine PLP1 missense variant differentiates oligodendrocyte maturation in connatal and classical Pelizaeus–Merzbacher disease - Rodrigo Gutierrez-Quintana; Paul Montague; Angie Rupp; Tosso Leeb; Jacques Penderis; Niamh Byrne; Veronica Gonzalo-Nadal; Ben August; Margaret Mullin; Jennifer Barrie; Julia M. Edgar; Ian D. Duncan; et al. (Proceedings of the National Academy of Sciences, 2026)
Pelizaeus–Merzbacher disease (PMD) is an X-linked hypomyelinating disorder caused by pathogenic variants in the proteolipid protein ( PLP1 ) gene. We report a spontaneous canine dysmyelinating leukodystrophy in English Cocker Spaniel puppies. The most severely affected male pup displayed pronounced generalized tremors, progressive motor dysfunction, and markedly impaired growth. Histopathology at 5 wk of age revealed profound central nervous system (CNS) dysmyelination with no evidence of peripheral nerve involvement. Western blotting confirmed markedly reduced expression of CNS myelin-associated proteins. Ultrastructural analysis demonstrated a near absence of compact myelin, rare myelinated axons, and significant oligodendrocyte abnormalities, the majority of which had an immature cellular morphology. More mature, yet infrequent oligodendrocytes had distended rough endoplasmic reticula. Nucleotide sequence analysis identified a hemizygous c.92T>A missense variant in the PLP1 gene predicted to cause a leucine-to-glutamine substitution in the first transmembrane domain, p.(L31Q). This variant was absent in over 1,600 public canine genomes and was predicted to be deleterious by multiple bioinformatic tools. Heterozygous females exhibited variable, transient clinical signs. We compared this canine leukodystrophy with the previously reported shaking pup and found that it represents a more severe phenotype recapitulating key clinical, pathological, and molecular features of severe connatal PMD in humans, including extreme CNS dysmyelination and associated neurological deficits. Interestingly, this genetic variant seems to cause a defect at the oligodendrocyte progenitor stage limiting subsequent oligodendrocyte maturation and preventing myelination. The identification of this naturally occurring model provides a potential resource for investigating the mechanisms and therapeutic targets for specific PLP1 genetic variants.